2021
DOI: 10.5194/gmd-14-521-2021
|View full text |Cite
|
Sign up to set email alerts
|

Numerical model to simulate long-term soil organic carbon and ground ice budget with permafrost and ice sheets (SOC-ICE-v1.0)

Abstract: Abstract. The degradation of permafrost is a large source of uncertainty in understanding the behaviour and projecting the future impacts of Earth's climate system. The spatial distributions of soil organic carbon (SOC) and ground ice (ICE) provide essential information for the assessment and projection of risks and impacts of permafrost degradation. However, uncertainties regarding the geographical distribution and estimated range of the total amount of stored carbon and ice are still substantial. A numerical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 100 publications
(156 reference statements)
0
4
0
Order By: Relevance
“…The compiled observations represented ground ice content at one point of time, and we did not consider the potential changes in ice content over time. Whatsoever, considering that accumulation of ground ice at the targeted depth range has typically occurred during several millennia (e.g., Saito et al, 2021) we argue that any aggradation of ground ice over annual to decadal periods would have had a small effect on the average ice content across the entire depth range. For example, Kokelj and Burn (2003) found that a decadal-scale ice aggradation of segregated ice beneath the permafrost table was 395 limited, and that the aggraded permafrost had similar ice content to that in underlying permafrost.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…The compiled observations represented ground ice content at one point of time, and we did not consider the potential changes in ice content over time. Whatsoever, considering that accumulation of ground ice at the targeted depth range has typically occurred during several millennia (e.g., Saito et al, 2021) we argue that any aggradation of ground ice over annual to decadal periods would have had a small effect on the average ice content across the entire depth range. For example, Kokelj and Burn (2003) found that a decadal-scale ice aggradation of segregated ice beneath the permafrost table was 395 limited, and that the aggraded permafrost had similar ice content to that in underlying permafrost.…”
mentioning
confidence: 79%
“…Ground ice content has also been simulated by process-based land surface models. For example, Saito et al (2021) used a land surface model to simulate long-term ground ice budget across the circumarctic permafrost region. Others have used the IPA map (Brown et al, 1997) to derive excess ice estimates at coarse resolution for land surface model simulations (e.g., Lee et al, 2014;Cai et al, 2020).…”
mentioning
confidence: 99%
“…The spatialization of permafrost ground ice is challenging. Accumulation of ground ice in the target depth range typically developed over thousands of years [51], and its distribution patterns are related to climatic, hydrological, and geomorphological characteristics over that time period. Although the predicted results based on contemporary climate and geomorphological conditions performed well in the RF model validation, the performance in practical applications (e.g., in evaluating the impacts of ground ice meltwater on the basin water balance) is difficult to directly assess.…”
Section: Discussionmentioning
confidence: 99%
“…Permafrost C stocks, biodegradability, and emission of permafrost carbon are baselines of simulating permafrost C feedback to climate warming. Their studies can help make alerts for the risks of environmental changes and assure the economic and productive safety for policy makers [115][116][117][118][119][120][121][122][123][124][125][126][127][128][129].…”
Section: Modeling and Projecting Permafrost Carbon Feedback To Climate Warmingmentioning
confidence: 99%